2010
DOI: 10.5370/jeet.2010.5.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic ATC Computation for Real-Time Power Markets

Abstract: -In this paper, a novel dynamic available transfer capability (DATC) has been computed for real time applications using three different intelligent techniques viz. i) back propagation algorithm (BPA), ii) radial basis function (RBF), and iii) adaptive neuro fuzzy inference system (ANFIS) for the first time. The conventional method of DATC is tedious and time consuming. DATC is concerned with calculating the maximum increase in point to point transfer such that the transient response remains stable and viable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Despite the ATC definition that should incorporate stability constraints for a set of postulated contingencies, literature survey has shown that most of the methodologies employed in ATC calculations are based on steady‐state viability. Few methods evaluate ATC by considering full representation of the power system dynamic behavior within the time frame of the transient stability.…”
Section: Available Transfer Capability Determination Methodsmentioning
confidence: 99%
“…Despite the ATC definition that should incorporate stability constraints for a set of postulated contingencies, literature survey has shown that most of the methodologies employed in ATC calculations are based on steady‐state viability. Few methods evaluate ATC by considering full representation of the power system dynamic behavior within the time frame of the transient stability.…”
Section: Available Transfer Capability Determination Methodsmentioning
confidence: 99%
“…The dynamic ATC for a system for any transaction can be considered as an approximation of the static ATC [39]. A comparative analysis of static and dynamic ATC has been done for different cases and reported in Table 15.…”
Section: Atc and Dynamic Atcmentioning
confidence: 99%